Analisa Instrumen Keuangan Perbankan Syariah Studi Kasus PT Bank Tabungan Negara. Tbk - Yulias Hidayah; Misnawati Misnawati; Rendy Diaz Hilrian; Adinda Nurul Rahmadyan; Finia Novarisy Zultia; Sari Dewi (Jurnal Mutiara Ilmu Akuntansi, 2024)
Islamic financial institutions use an accounting system that is different from conventional accounting. The basis of sharia banking accounting follows the principles of Islamic economics which include the prohibition of interest or what is often called usury (including other usurious practices), then the prohibition of investment in businesses that are considered haram, as well as encouraging fair wealth and economic growth.